Pokrajinska imena kot dejavnik identitete - Geršič, Matjaž (Geografija Slovenije, 2020)
This volume focuses on the names of Slovenian regions and how they are connected with regional identity. The introduction defines the basic terms and provides an overview of Slovenian research on geographical names. The second part chronologically outlines the sources of the names of regions, starting with archival material. This is followed by an overview of modern maps and registers by the Slovenian Surveying and Mapping Authority (GURS), and, finally, geographical regionalizations are presented as a source of the names of regions. The third part presents the results of collecting the names of regions as part of a survey. The findings show the following: the names of regions reflect regional identity and represent an important factor in the residents' minds, they are not hierarchically structured, the majority are deeply rooted among people, some are disappearing, and the share of newly established names is negligible. In people's minds, the names of regions have an unclearly defined denotation or scope and, like other linguistic elements, change over time.